An integrated approach with the zebrafish model for biomonitoring of municipal wastewater effluent and receiving waters. (15th March 2018) - Li, Caixia; Chen, Qiyu; Zhang, Xiaoyan; Snyder, Shane A.; Gong, Zhiyuan; Lam, Siew Hong
Abstract: Comprehensive monitoring of water pollution is challenging. With the increasing amount and types of anthropogenic compounds being released into water, there are rising concerns of undetected toxicity. This is especially true for municipal wastewater effluents that are discharged to surface waters. This study was designed to integrate zebrafish toxicogenomics, targeted gene expression, and morphological analyses, for toxicity evaluation of effluent discharged from two previously characterized wastewater treatment plants (WWTPs) in Pima County, Arizona, and their receiving surface water. Zebrafish embryos were exposed to organic extracts from the WWTP1 effluent that were reconstituted to represent 1× and 0.5× of the original concentration. Microarray analyses identified deregulated gene probes that mapped to 1666, 779, and 631 unique human homologs in the 1×, 0.5×, and the intersection of both groups, respectively. These were associated with 18 cellular and molecular functions ranging from cell cycle to metabolism and are involved in the development and function of 10 organ systems including nervous, cardiovascular, haematological, reproductive, and hepatic systems. Superpathway of cholesterol biosynthesis, retinoic acid receptor activation, glucocorticoid receptor and prolactin signaling were among the top 11 perturbed canonical pathways. Real-time quantitative PCR validated the expression changes of 12 selected genes. These genes were then tested on zebrafish embryos exposed to the reconstituted extract of water sampled downstream of WWTP1 and another nearby WWTP2. The expression of several targeted genes were significantly affected by the WWTP effluents and some of the downstream receiving waters. Morphological analyses using four transgenic zebrafish lines revealed potential toxicity associated with nervous, hepatic, endothelial-vascular and myeloid systems. This study demonstrated how information can be obtained using adverse outcome pathway framework to derive biological effect-based monitoring tools. This integrated approach using zebrafish can supplement analytical chemistry to provide more comprehensive monitoring of discharged effluents and their receiving waters. Graphical abstract: Highlights: Zebrafish toxicogenomics, targeted genes and morphology for biomonitoring. Effluent exposure deregulated 631 genes at 0.5× and 1.0× original concentration. Genes linked to 18 molecular functions, 10 organ-systems and 11 signaling pathways. Effluent exposure affected nervous, hepatic, and vascular-myeloid systems. Integrated effect-based biomonitoring tools for effluent and receiving waters.